Approaches to supporting and measuring mathematical problem posing: a systematic review of interventions in mathematics education - Zhang, L; Stylianides, A; Stylianides, G (Springer, 2025)
Mathematical problem posing, a form of authentic mathematical inquiry and creation, has been acknowledged as important by educators and curriculum frameworks internationally and has been the focus of several intervention studies with students and teachers. However, the intervention components and measured outcomes of these prior studies varied, highlighting the diverse approaches researchers have taken to support and measure mathematical problem-posing competence. In this systematic review, we examined 39 intervention studies published over the past three decades, all aimed at developing mathematical problem-posing competence, and we identified nine common intervention components suggested or utilized within these studies. Also, we derived clusters of measured outcomes related to mathematical problem-posing competence used in the interventions. Our findings deepen understanding of approaches to supporting and measuring mathematical problem-posing competence, thus casting light on what works, including methods for measuring progress, in problem-posing interventions. We discuss implications of our findings for future research and practice.